2001
DOI: 10.1111/j.1540-6288.2001.tb00011.x
|View full text |Cite
|
Sign up to set email alerts
|

Combining Bond Rating Forecasts Using Logit

Abstract: Companies sometimes use statistical analysis to anticipate their bond ratings or a change in the rating. However, different statistical models can yield different ratings forecasts, and there is no clear rule for which model is preferable. We use several forecasting methods to predict bond ratings in the transportation and industrial sectors listed by Moody's bond rating service. A variant of the ordered-logit regression-combining method of Kamstra and Kennedy 1998 yields statistically significant, quantitativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
67
0
13

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(84 citation statements)
references
References 49 publications
4
67
0
13
Order By: Relevance
“…Profitability which proxied through the Net Profit Margin (NPM) has sig 0.000 <0.05 and indicates that profitability affect the bond ratings. These results are consistent with research conducted by Kamstra et al, (2001), Kim and Gu (2004), Magreta andNurmayanti (2009), Amalia (2012), Melani and Kananlua (2013), Septyawanti (2013), as well as Sunarjanto and Tulasi (2013).…”
Section: The Effect Of Profitability To the Bond Ratingsupporting
confidence: 81%
See 3 more Smart Citations
“…Profitability which proxied through the Net Profit Margin (NPM) has sig 0.000 <0.05 and indicates that profitability affect the bond ratings. These results are consistent with research conducted by Kamstra et al, (2001), Kim and Gu (2004), Magreta andNurmayanti (2009), Amalia (2012), Melani and Kananlua (2013), Septyawanti (2013), as well as Sunarjanto and Tulasi (2013).…”
Section: The Effect Of Profitability To the Bond Ratingsupporting
confidence: 81%
“…Therefore, the high level of liquidity is affect to the better bond rating. Kamstra et al, (2001), Kim and Gu (2004), Magreta andNurmayanti (2009), Amalia (2012), Melani and Kananlua (2013), Septyawanti (2013), and Sunarjanto and Tulasi (2013) revealed that profitability is affect to the bond rating. If the firm's income become higher, then the firm's ability to pay all its liabilities become higher so the deafult risk become lower and the bond rating getting better too.…”
Section: Leverage and Bond Ratingmentioning
confidence: 99%
See 2 more Smart Citations
“…but also provide information about their future financial positions. There has been extensive research in predicting bond ratings using multi-variate discriminant analysis, ordered choice models, non-parametric techniques and combined methods' forecasts to predict bond ratings -see, Altman and Saunders, (1998), Kamstra et al (2001) and Kim (2005). Thus, we employ financial variables, in addition to country risk (which we model using country specific dummy variables), as determinants of bank ratings in our modelling.…”
Section: Introductionmentioning
confidence: 99%